Personality traits, intrinsic motivation and job performance among newly appointed JKR officers in Klang Valley area - Mohd Asri, Md Isa (2014)
This quantitative research paper aims to determine the relationship between personality traits, intrinsic motivation and job performance among newly appointed JKR officers in the Klang Valley area. Respondents for this research comprised of 135 newly appointed JKR officers. Data were analysed using Statistical Package For Social Sciences (SPSS) Version 17 software. Tests conducted were Pearson Correlation analysis and Simple Linear Regression analysis. The correlation analysis results suggest that personality traits and intrinsic motivation have a significant positive linear relationship with job performance with moderate strength of association. Subsequently, the multiple regression result shows the value of coefficient determination of 0.304 which concluded that only 30.4% of the job performances were influenced by personality traits and intrinsic motivation and 69.6% was explained by other factor that was not involved in this research. Further, given standardized coefficient (13) of 0.333 for relatedness and 0.243 for agreeableness with significance values for both dimensions are less than 0.05, a low degree significant positive relationships between relatedness with job performance is reported. This shows that for every increase of relatedness and agreeableness, job performance will also increase significantly. Recommendations were also being suggested for the JKR organization to to emphasise on programme and training in character building on their officers parallel with the technical competency.